Understanding the Experiences of Low-Income Individuals Receiving Farmers' Market Incentives in the United States: A Qualitative Study. Issue 6 (November 2017) - Savoie Roskos, Mateja R.; Wengreen, Heidi; Gast, Julie; LeBlanc, Heidi; Durward, Carrie
Objective . The objective of this study was to identify benefits and barriers to using a farmers' market (FM) incentive program among program participants. Design . In qualitative semistructured interviews, participants were asked about their experiences with shopping at FM, using FM incentives, barriers to fruit and vegetable (F&V) intake, and changes in dietary intake. Interviews were recorded and transcribed. Inductive content analysis was used to code, categorize, and develop themes based on the transcriptions. Setting . A FM in Northern Utah. Subjects. A convenience sample of participants ( n = 14) completed a 45- to 60-minute interview after receiving FM incentives for an 8-week intervention period. Results . FM incentives reduced barriers associated with shopping at FM such as cost and accessibility among program participants. Incentives provided participants with greater spending flexibility, allowing parents to provide children with F&V that previously did not fit into their food budget. Participants reported greater family and community involvement when shopping at FM. However, the limited hours and days of operation were factors that reduced the use of FM among participants, even when incentives were provided. Conclusions . The perceived benefits and barriers to shopping at FM and receiving FM incentives should be considered by future programmers and funding agencies.